2019
DOI: 10.1155/2019/1529137
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behaviour of Cast‐In‐Situ Phosphogypsum‐Reinforced Concrete Grid Frame Composite Walls

Abstract: This paper mainly studies the effect of cast-in-situ phosphogypsum on seismic behaviour of reinforced concrete grid frame. The mechanical behaviour of three reinforced concrete grid frames and four cast-in-situ phosphogypsum-reinforced concrete grid frame composite walls under low cycle alternating load was designed and tested. The test results show that the reinforced concrete grid frame has less bearing capacity and poor energy consumption. The addition of cast-in-situ phosphogypsum can effectively improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The results indicated that the bearing capacity of the composite wall was increased by 134.4% due to the phosphogypsum infill, and the hysteresis and energy dissipation capabilities were higher than CGF. Lu et al 8 obtained a similar conclusion to Wu et al 14 through the horizontal load cycle tests on composite walls. Nevertheless, references 8,14 mainly focused on the mechanical properties of composite wall, ignoring the synergism between CGF and filled wall.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The results indicated that the bearing capacity of the composite wall was increased by 134.4% due to the phosphogypsum infill, and the hysteresis and energy dissipation capabilities were higher than CGF. Lu et al 8 obtained a similar conclusion to Wu et al 14 through the horizontal load cycle tests on composite walls. Nevertheless, references 8,14 mainly focused on the mechanical properties of composite wall, ignoring the synergism between CGF and filled wall.…”
Section: Introductionsupporting
confidence: 60%
“…Lu et al 8 obtained a similar conclusion to Wu et al 14 through the horizontal load cycle tests on composite walls. Nevertheless, references 8,14 mainly focused on the mechanical properties of composite wall, ignoring the synergism between CGF and filled wall. Therefore, the interaction between CGF and filling wall needed further study.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations